Sustainable (–)-Ambrox Production: Chemistry Meets Biocatalysis - Eric Eichhorn; Boris Schilling; Agnes Bombrun; Fridtjof Schroeder (CHIMIA)
(–)-Ambrox, the most prominent olfactive component of ambergris, is one of the most widely used biodegradable fragrance ingredients. It is traditionally produced from the diterpene sclareol chemically modified and cyclized into (–)-ambrox. The availability of the new feedstock (E)-β-farnesene produced by fermentation opened new routes to (E,E)-homofarnesol as a precursor to (–)-ambrox. Combining the chemical transformation of (E)-β-farnesene to (E,E)-homofarnesol and its enzymatic cyclization with an engineered Squalene Hopene Cyclase provided a new sustainable route for the production of (–)-ambrox at industrial scale. Compared to the traditional synthesis from sclareol, the new and innovative route from (E)-β-farnesene improves atom and step economy, reduces waste production, solvent and energy consumption.